Towards diversity in young adult fiction: Australian YA authors' publishing experiences and its implications for YA librarians and readers' advisory services. Issue 3 (3rd July 2018) - Booth, Emily; Narayan, Bhuva
ABSTRACT: Based on a study of Australian young adult (YA) fiction authors, this paper argues that it is necessary for publishers, booksellers, and YA librarians to pay attention to the global movement towards diversity: diversity within their own organisations, diversity among authors they publish, stock, or collect, and representations of diversity within YA fiction. The mainstream attention to diversity has particularly focused on media for young people, with advocates stating that children and teenagers from traditionally marginalised communities deserve to see their own experiences reflected and validated in the media they consume. This paper looks at diversity in writing and traditional publishing through interviews with Australian YA authors (conducted in 2016) from traditionally marginalised or unacknowledged communities, especially as it relates to their transition from reader to writer, and their experience of the publishing journey. A critical discourse analysis of the interviews point to a need for more diversity representations in YA fiction, and also the need for a change in industry practices to enable this, including publishing, bookselling, and library practices. Abbreviations : YA - Young Adult Fiction WNDB - We Need Diverse Books CDA - Critical Discourse Analysis